Effects of calcium and phosphate on uranium(IV) oxidation: Comparison between nanoparticulate uraninite and amorphous UIV–phosphate. (1st February 2016) - Latta, Drew E.; Kemner, Kenneth M.; Mishra, Bhoopesh; Boyanov, Maxim I.
Abstract: The mobility of uranium in subsurface environments depends strongly on its redox state, with U IV phases being significantly less soluble than U VI minerals. This study compares the oxidation kinetics and mechanisms of two potential products of U VI reduction in natural systems, a nanoparticulate UO2 phase and an amorphous U IV –Ca–PO4 analog to ningyoite (CaU IV (PO4 )2 ·1–2H2 O). The valence of U was tracked by X-ray absorption near-edge spectroscopy (XANES), showing similar oxidation rate constants for U IV O2 and U IV –phosphate in solutions equilibrated with atmospheric O2 and CO2 at pH 7.0 ( k obs, UO2  = 0.17 ± 0.075 h −1 vs. k obs, U IV PO4  = 0.30 ± 0.25 h −1 ). Addition of up to 400 μM Ca and PO4 decreased the oxidation rate constant by an order of magnitude for both UO2 and U IV –phosphate. The intermediates and products of oxidation were tracked by electron microscopy, powder X-ray diffraction (pXRD), and extended X-ray absorption fine-structure spectroscopy (EXAFS). In the absence of Ca or PO4, the product of UO2 oxidation is Na–uranyl oxyhydroxide (under environmentally relevant concentrations of sodium, 15 mM NaClO4 and low carbonate concentration), resulting in low concentrations of dissolved U VI (<2.5 × 10 −7  M). Oxidation of U IV –phosphate produced a Na-autunite phase (Na2 (UO2 )PO4 · x H2 O), resulting in similarly low dissolved U concentrations (<7.3 × 10 −8  M). When Ca and PO4 are present in the solution, the EXAFS data and the solubility of the U VI phase resulting from oxidation of UO2 and U IV –phosphate are consistent with the precipitation of Na-autunite. Bicarbonate extractions and Ca K-edge X-ray absorption spectroscopy of oxidized solids indicate the formation of a Ca–U VI –PO4 layer on the UO2 surface and suggest a passivation layer mechanism for the decreased rate of UO2 oxidation in the presence of Ca and PO4 . Interestingly, the extractions were unable to remove all of the oxidized U from partially oxidized UO2 solids, suggesting that oxidized U is distributed between the interior of the UO2 nanoparticles and the labile surface layer. Accounting for the entire pool of oxidized U by XANES is the likely reason for the higher UO2 oxidation rate constants determined here relative to prior studies. Our results suggest that the natural presence or addition of Ca and PO4 in groundwater could slow the rates of U IV oxidation, but that the rates are still fast enough to cause complete oxidation of U IV within days under fully oxygenated conditions.